Test-Retest Reliability of the Muslim Religiosity Scale: Follow-Up to Religious Involvement and Health Among Dialysis Patients in Saudi Arabia - Zaben, Faten Al (Journal of religion and health, 2015)
The intra-class correlation coefficient for the scale was 0.961, 95 % CI 0.912-0.983. We conclude that the MRS is a highly reliable measure of Muslim religiosity over time.